Systemic inflammation response index predicts 3-month outcome in patients with mild acute ischemic stroke receiving intravenous thrombolysis - Chu, Min; Luo, Yunhe; Wang, Daosheng; Liu, Yang; Wang, Delong; Wang, Yong; Zhao, Jing (Frontiers in Neurology, 2023)
Introduction A crucial aspect of stroke progression is the inflammatory response. As novel inflammatory and prognostic markers, the systemic immune inflammation index (SII) and the systemic inflammation response index (SIRI) have recently been studied. The objective of our study was to evaluate the prognostic value of SII and SIRI in mild acute ischemic stroke (AIS) patients following intravenous thrombolysis (IVT). Methods Our study screened the clinical data of patients with mild AIS admitted to the Minhang Hospital of Fudan University for retrospective analysis. The SIRI and SII were examined by the emergency laboratory before IVT. Functional outcome was evaluated 3 months after the onset of stroke using the modified Rankin Scale (mRS). mRS ≥ 2 was defined as an unfavorable outcome. The relationship between SIRI and SII and the 3-month prognosis was determined using both univariate and multivariate analysis. Receiver operating characteristic curve was performed to evaluate the predictive value of SIRI for AIS prognosis. Results A total of 240 patients were included in this study. Both SIRI and SII were higher in the unfavorable outcome group than in the favorable outcome group [1.28 (0.70–1.88) vs. 0.79 (0.51–1.08), P < 0.001 and 531.93 (377.55–797.12) vs. 397.23 (263.32–577.65), P < 0.001]. Multivariate logistic regression analyses showed that SIRI was significantly associated with 3-month unfavorable outcome of mild AIS patients [odds ratio (OR) = 2.938, 95% confidence interval (CI) = 1.805–4.782, P < 0.001], conversely, SII had no prognostic value. When SIRI combined with the established clinical factors, the area under the curve (AUC) showed a significant improvement (0.773 vs. 0.683, P for comparison = 0.0017). Conclusions Higher SIRI could be valuable in predicting poor clinical outcomes for patients with mild AIS following IVT.